Brain-derived neurotrophic factor and its related enzymes and receptors play important roles after hypoxic-ischemic brain damage - Liu-Lin Xiong; Jie Chen; Ruo-Lan Du; Jia Liu; Yan-Jun Chen; Mohammed Al Hawwas; Xin-Fu Zhou; Ting-Hua Wang; Si-Jin Yang; Xue Bai (Neural Regeneration Research, 2021)
Brain-derived neurotrophic factor (BDNF) regulates many neurological functions and plays a vital role during the recovery from central nervous system injuries. However, the changes in BDNF expression and associated factors following hypoxia-ischemia induced neonatal brain damage, and the significance of these changes are not fully understood. In the present study, a rat model of hypoxic-ischemic brain damage was established through the occlusion of the right common carotid artery, followed by 2 hours in a hypoxic-ischemic environment. Rats with hypoxic-ischemic brain damage presented deficits in both sensory and motor functions, and obvious pathological changes could be detected in brain tissues. The mRNA expression levels of BDNF and its processing enzymes and receptors (Furin, matrix metallopeptidase 9, tissue-type plasminogen activator, tyrosine Kinase receptor B, plasminogen activator inhibitor-1, and Sortilin) were upregulated in the ipsilateral hippocampus and cerebral cortex 6 hours after injury; however, the expression levels of these mRNAs were found to be downregulated in the contralateral hippocampus and cerebral cortex. These findings suggest that BDNF and its processing enzymes and receptors may play important roles in the pathogenesis and recovery from neonatal hypoxic-ischemic brain damage. This study was approved by the Animal Ethics Committee of the University of South Australia (approval No. U12-18) on July 30, 2018.